The Local Wisdom of Lanna Musical Instrument for Inherit the making Lanna Musical Instrument and Support the Strengthening Culture - Jaila, Buranapan (Community and Social Development Journal, 2020)
Salor and Sueng is an Lanna musical instrument and popular to play in present day. The quality of musical instrument is depend on material for making and musical instrument maker skill. This research aims to study the development of Lanna music making knowledge transmission from Master Boonrat Tippayarat, Lanna musical instrument maker in Chiang Mai province and the process of making Lanna musical instrument. Ethnomusicological method used for this study. The result of this research shows the first standard Lanna musical instrument maker is Jao Suntorn Na Chiang Mai and transmit to Master Boonrat Tippayarat. The process of learning to make musical instrument by observation and practice by doing. Master Boonrat Tippayarat transmit the musical instrument making to Master Khamjorn Thevokut, specialize to make Salor and Sueng in the present day. The process of Salor and Sueng making; small size, medium size and large size making is difference by nature of musical sound.